Biological characteristic of Chrysopodes spinella (Neuroptera: Chrysopidae) fed with Bemisia tabaci eggs (Hemiptera: Aleyrodidae) - Ortega, E. S. (2013)
The whitefly Bemisia tabaci (Hemiptera: Aleyrodidae) is one of the insect pests of greatest economic importance worldwide. Among its natural enemies, we find members of the Chrysopidae family (Neuroptera). The objective of this work was to determine some biological characteristics of Chrysopodes spinella fed with whitefly eggs under laboratory conditions. C. spinella adults were collected in tomato greenhouses, in Lules, Tucumán, Argentina, and taken to EEAOC laboratories. 34 larvae were fed with whitefly eggs and 37 with Sitotroga cerealella eggs, used as control. They were offered a new number off eggs every 24 hours and larvae survival was recorded. Oviposition and longevity were recorded when they reached the adult stage. The development time of C. spinella fed with whitefly eggs was 35 days and 45 days with S. cerealella eggs. Survival of immature stages, number of eggs per adult and their longevity were higher when C. spinella was fed with S. cerealella eggs. The results obtained in this work are an important contribution to a better understanding of this predator species.